A new species of Panochthus Burmeister (Xenarthra, Cingulata, Glyptodontidae) from the Pleistocene of the Eastern Cordillera, Bolivia - Zurita, Alfredo Eduardo (2017)
Panochthus and Glyptodon are the Pleistocene Glyptodontidae having the greatest range of latitudinal distribution and elevation in South America. The most recent revisions of Panochthus recognized its high taxonomic diversification mainly distributed in the Chaco-Pampean region of Argentina, Uruguay, southern Bolivia and southern and north-eastern Brazil, while the Andean records are poorly known. This contribution aims: (a) to describe a new species of Panochthus from the Pleistocene of the surroundings of Potosi (Bolivia), which represents one of the highest known elevation records for fossil Xenarthra; (b) to carry out a phylogenetic analysis in order to test its location in Panochthus and relationship to some allied genera; (c) to discuss some palaeobiogeographical and morphological implications. The results show that, in agreement with previous studies, Panochthus is a natural group, being Propanochthus the sister taxa. This conclusion agrees, at least in part, with the original interpretation of Burmeister, who recognized Pr. bullifer as belonging to Panochthus. The genera Nopachtus and Phlyctaenopyga are more closely related to some ‘Plohophorini’ than to the clade Propanochthus + Panochthus. Within Panochthus, this new species occupies a relatively basal position as a sister taxon of the clade composed of P. tuberculatus, P. intermedius, and P. greslebini.